PENGARUH NON PERFORMING LOAN (NPL) DAN CAPITAL ADEQUACY RATIO (CAR) TERHADAP RETURN ON ASSETS (ROA) PADA BANK BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Didin Rasyiddin Wahyu; Iis Nurasiah; Sri Rahayu (LP2M Universitas Bina Bangsa, 2023)
The purpose of the study was to determine whether NPL and CAR affect the ROA of state-owned banks listed on the Indonesia Stock Exchange (IDX) for the 2012-2019 period. This research method uses quantitative research methods, the population in this study is all 4 state-owned banks and the samples used are 4 state-owned banks using saturated samples or saturation sampling, data collection techniques using secondary data, data analysis techniques used in this study consist of statistical descriptions, classical assumption tests, multiple linear regression analysis, coefficient of determination and statistical hypothesis. Based on the results of the study, it is known that the NPL tcount is -7.678 < ttable -2.045 and the t-test sig is 0.000 < 0.05, the CAR tcount value is 1,113 < ttable 2,045 and the t-test sig is 0.275 > 0.05. And the F test result (simultaneous) obtained Fcalculate of 30.235 > 3.33 Ftable and the sig value of the F test 0.000 < 0.05. thus it can be concluded that partially NPL affects ROA and CAR does not affect ROA while simultaneously NPL and CAR affect ROA at state-owned banks listed on the Indonesia Stock Exchange for the 2012-2019 period